1975
DOI: 10.1007/bf01318240
|View full text |Cite
|
Sign up to set email alerts
|

Abortive rabies in rabbits and white rats infected intracerebrally

Abstract: Non-fatal rabies was successfully reproduced in rabbits infected intracerebrally with a highly pathogenic strain of street virus isolated from a man who had died of hydrophobia abter a dog bite and in white rats infected intracerebrally with the CVS strain of fixed virus. All the animals were pretreated with a sublethal intraperitoneal dose of live rabies virus. The surviving animals showed residual neurological symptoms (except one rat) in the form of paresis (both mild and marked) and high titres of virus-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In another report, two of the dogs, inoculated with a rabies virus strain from Ethiopia recovered from clinical rabies [27]. In other words, rabies carrier state or inapparent infection and the presence of rabies antigens and antibodies in apparently healthy dogs have been a subject of research in Nigeria and elsewhere in the world [16,20,21,22,23,28,29,30,31]. Additional research, however, is necessary to answer these questions.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, two of the dogs, inoculated with a rabies virus strain from Ethiopia recovered from clinical rabies [27]. In other words, rabies carrier state or inapparent infection and the presence of rabies antigens and antibodies in apparently healthy dogs have been a subject of research in Nigeria and elsewhere in the world [16,20,21,22,23,28,29,30,31]. Additional research, however, is necessary to answer these questions.…”
Section: Discussionmentioning
confidence: 99%
“…When recovery has occurred, the majority of cases were left with permanent neurologic sequelae and severe cognitive disability [79]. In experimental infection of animals, recovery has been recorded in a number of species, including mice [17,66,80], dogs [81], a ferret [82], and rabbits [83]. As with human cases, the majority of these individuals had lasting sequelae following recovery.…”
Section: Recoverymentioning
confidence: 99%
“…To achieve this goal, a joint project of WHO–OIE–FAO was announced in 2015 to control animal–human–ecosystems rabies interface [5] , [20] , [21] , [22] . It was previously suggested that different forms of rabies infections exist in nature according to the invading virus [23] . While infection with paralytic rabies virus (PRV) results in dog paralysis within 6 days, the convulsive rabies viruses (CRV) induces convulsions in dogs after a longer incubation period [24] .…”
Section: History Distribution and Transmission Of The Diseasementioning
confidence: 99%